IT CONSULTING: CONTENT, ESSENCE, TYPES - SALUN, Maryna; MURAKHOVSKYI, Valerii; PEDCHENKO, Valeria (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to a comprehensive analysis of IT consulting in the context of modern business’s dynamic digital transformation. The purpose of the study is not only to generalize the theoretical foundations but also to apply the classification of types of IT consulting in practice to improve the efficiency of business processes, especially in the small and medium-sized enterprise sector. The article reveals the versatility of IT consulting, covering a wide range of services from strategic planning to operational technical support. It starts with an analysis of various definitions. The comparative analysis of the definitions presented in the article allows us to highlight the key characteristics of IT consulting, such as focus, object, goals, and approaches to providing services, which is critically important for understanding its essence. The central aspect of the article is the systematization of types of IT consulting. The classification is carried out according to various criteria, including types of services (audit, strategy development, technology implementation, project management, technical support), areas of application (finance, manufacturing, retail, healthcare), project stages (preliminary analysis, concept development, design, implementation, support) and types of clients (large corporations, small and medium-sized businesses, startups). Special attention is paid to analyzing each of the selected types of IT consulting, as well as their characteristics and features, which allows enterprises to build effective digital transformation strategies. The article emphasizes that the choice of a specific type of IT consulting should be determined by the specifics of the business, the size of the company, the stage of its development, and the available budget. The conclusions emphasize that IT consulting is an integral part of modern business, contributing to increasing enterprises’ competitiveness and sustainability in the face of rapid technological change. Effective use of IT consulting allows enterprises to optimize internal processes and adapt to external challenges, using the latest technologies to achieve strategic goals.